Why Inclusive Resources Matter-The Importance of Inclusive Internal Resources for Strain and Intended Inclusive Practices of Pre-Service Teachers - Birte Oetjen (MDPI AG, 2023)
Inclusive internal resources moderate teachers' mental health and predict teachers' inclusive practices. Therefore, it is important to enhance inclusive internal resources during the beginning of initial teaching experiences. Applying the job demands-resources (JD-R) theory to explain strain and the theory of planned behavior to elucidate behavior, it can be assumed that teachers' inclusive resources lead to a reduction in negative strain, an increase in positive strain and efficient (intended) inclusive practices as occupational outcomes. However, there is a lack of scientific evidence to support this assumption among pre-service teachers. To ensure that student teachers had teaching experiences in inclusive settings, the present study was conducted after pre-service teachers' final teaching practicum in the university phase of teacher education. A total of 294 pre-service elementary school teachers from one university in Germany participated. Structural equation models suggested that inclusive self-efficacy expectations and attitudes towards inclusion predicted students intended inclusive practices, but so did professional engagement as a positive strain. While professional engagement only correlated with inclusive self-efficacy expectations, the self-perceived stress intensity of a challenging student as negative strain negatively correlated with inclusive self-efficacy expectations and personal resistance.